Lignin-based carbon aerogel as well as preparation method and application thereof
Photosensitive and hydrophobic oil-absorbing lignin-based carbon aerogels are prepared by using eutectic solvents synthesized by lactic acid and choline chloride in lignin-based carbon aerogels, with specific additives and specific preparation steps, and a photosensitive and hydrophobic oil-absorbing lignin-based carbon aerogels, with the addition of specific additives and performing specific preparation steps. , the problem of low oil-water separation efficiency of carbon aerogels in the prior art has been solved, efficient adsorption and oil-water separation are achieved, and the preparation cost is reduced.
Patent Information
- Application Number
- CN202411541655.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The existing carbon aerogels are inefficient in oil-water separation in seawater, and the preparation process of lignin-based carbon aerogels is complex and costly, and the structure and performance need to be further optimized.
The photosensitive and hydrophobic lignin-based carbon aerogel is prepared by using eutectic solvents synthesized by lactic acid and choline chloride. By adding alkali lignin, resorcinol, formaldehyde solution, pore-forming agent, photothermal sensing The agent and hydrophobic agent are prepared with specific stirring, heating, carbonization and chemical vapor deposition steps to prepare carbon aerogels with excellent photothermal conduction and efficient adsorption properties.
It realizes efficient adsorption and oil-water separation of heavy oil leaked in seawater, reduces the viscosity of crude oil, improves adsorption efficiency, and has a simple preparation process and low cost, and the product has a good recycling rate.
Smart Images

Figure CN119461312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomass energy and carbon aerogels, and in particular to a light-sensitive and hydrophobic, oil-absorbing lignin-based carbon aerogel and a preparation method and application thereof, which are mainly used in the field of oil-water separation, such as adsorbing heavy oil leaked in seawater. Background Art
[0002] Environmental factors such as seawater pollution have caused a large amount of oily organic matter to enter the water, posing a threat to the environment and human health. Traditional carbon aerogels have uneven pore distribution, small adsorption capacity, and low separation efficiency, while biomass-based carbon aerogels have low cost and high efficiency, becoming a research hotspot. Biomass-based carbon aerogels are mostly made of cellulose, wood fiber, and biomass derivatives, while lignin is mostly discarded as waste. Therefore, the development of lignin-based carbon aerogels can improve the above situation to a certain extent.
[0003] Although lignin-based carbon aerogels have broad application potential as an effective porous material, there are still some problems. First, the process of preparing lignin-based carbon aerogels is relatively complicated, requiring the use of expensive catalysts and organic solvents, and the cost is high. Secondly, the structure and performance of lignin-based carbon aerogels still need to be further optimized, such as the uniformity of pore structure and the improvement of specific surface area. In addition, the repeatability and stability of lignin-based carbon aerogels are also a challenge. Therefore, preparing a pair of light-sensitive and hydrophobic oil-absorbing lignin-based carbon aerogels will become a good choice for solving seawater crude oil pollution. Summary of the invention
[0004] In view of this, the main purpose of the present invention is to provide a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel and its preparation method and application. The problem to be solved is how to provide a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel and apply it to adsorb heavy oil leaked in seawater, thereby reducing the viscosity of crude oil, promoting efficient adsorption of crude oil, and successfully achieving oil-water separation.
[0005] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a light-sensitive and hydrophobic oil-absorbing lignin-based carbon aerogel, which comprises the following raw materials by weight: 56-82 parts of lactic acid; 18-44 parts of choline chloride; 5-12.5 parts of alkali lignin; 5-12.5 parts of resorcinol; 30-40 parts of formaldehyde solution; 1-3 parts of pore-forming agent; 1-2 parts of photothermal sensor; 5-10 parts of hydrophobic agent.
[0006] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0007] Preferably, in the aforementioned light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, the concentration of the formaldehyde solution is 37 wt %; and the pore-forming agent is selected from one of zinc chloride, aluminum chloride and sodium chloride.
[0008] Preferably, in the aforementioned light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, the photothermal sensing agent is selected from one of nano-ferroferric oxide, graphene oxide and carbon nanotubes; the hydrophobic agent can be selected from one of methyltrichlorosilane, trimethylchlorosilane and triisopropylchlorosilane.
[0009] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0010] S1. Stir choline chloride and lactic acid to form a transparent solution; then add alkali lignin and resorcinol to the transparent solution and continue to stir until dissolved; then continue to add a pore-forming agent and continue to stir until dissolved; then add a photothermal sensor and perform ultrasound until the photothermal sensor is evenly dispersed; then drop a formaldehyde solution and stir evenly;
[0011] S2: heating the solution obtained in step S1 in a sealed environment until it is gelled, and then continuing to dry and age in an open environment;
[0012] S3 taking out the gel dried in step S2 and carbonizing it in the presence of an inert gas to form a carbon aerogel;
[0013] S4: subjecting the carbon aerogel obtained in step S3 to chemical vapor deposition in a dry environment using a hydrophobic agent to obtain the light-sensitive, hydrophobic, and oil-absorbing lignin-based carbon aerogel.
[0014] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0015] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S1, the stirring speed of the choline chloride and lactic acid is 100-200 r / min, and the stirring time is 20-40 min.
[0016] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S1, the stirring speed after adding the alkali lignin and resorcinol is 300-500 r / min, and the time is 20-40 min.
[0017] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S1, the stirring speed after adding the pore-forming agent is 500-600 r / min, and the time is 20-40 min.
[0018] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S1, the temperature of the ultrasound is 20-30° C., and the time is 10-20 min.
[0019] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S1, the stirring speed after adding the formaldehyde solution is 100-200 r / min, and the time is 10-20 min.
[0020] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S2, the temperature of the heating reaction is 85-105°C, and the time is 40-60 min; the temperature of the drying and aging is 85-105°C, and the time is 2-3 h.
[0021] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S3, the inert gas is selected from nitrogen, hydrogen, nitrogen, argon or helium with a purity of 99%; the carbonization parameters are set as follows: heating to 950-1000°C at a heating rate of 4-6°C / min, keeping warm for 1.5-3 hours, and then cooling to room temperature at a cooling rate of 1-2°C / min.
[0022] Preferably, in the aforementioned method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, in step S4, the hydrophobic agent is added as follows: 1-2 times every 1 hour, for a total of 4-6 times.
[0023] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a photosensitive and hydrophobic oil-absorbing lignin-based carbon aerogel for use in oil-water separation, wherein the lignin-based carbon aerogel comprises the following raw materials by weight: 56-82 parts of lactic acid; 18-44 parts of choline chloride; 5-12.5 parts of alkali lignin; 5-12.5 parts of resorcinol; 30-40 parts of formaldehyde solution; 1-3 parts of pore-forming agent; 1-2 parts of photothermal sensor; and 5-10 parts of hydrophobic agent.
[0024] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0025] Preferably, the aforementioned photosensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel is used in oil-water separation, wherein the adsorption rate of the lignin-based carbon aerogel for various oils and organic matter is 8.21g / g-10.1g / g, so that the recycling rate of the lignin-based carbon aerogel after 10 uses is 94%-95%.
[0026] By means of the above technical solution, the present invention provides a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel and a preparation method and application thereof, which have at least the following advantages:
[0027] 1. The present invention uses a low eutectic solvent synthesized from lactic acid and choline chloride to prepare lignin-based carbon aerogel, which can overcome the problem of large shrinkage caused by traditional aerogel preparation using water as solvent. In addition, the low eutectic solvent can also serve as a structural directing agent for the porous hierarchical structure of the aerogel and is easy to recycle.
[0028] 2. The present invention uses industrial alkali lignin as a partial substitute for resorcinol, replacing 50% of the original amount of resorcinol to prepare lignin-based carbon aerogel. Because alkali lignin has a similar chemical structure to resorcinol, is non-toxic, harmless to the environment, and inexpensive, it can not only reduce the preparation cost, but also reduce pollution to the environment.
[0029] 3. The present invention adds zinc chloride as a pore-forming agent, which can be uniformly dissolved in the gelation process and plays the role of an expander, a foaming agent, and a pore-forming agent in the carbonization process, thereby significantly increasing the specific surface area of the lignin-based carbon aerogel and significantly enhancing the oil absorption effect.
[0030] 4. The present invention adds nano-ferroferric oxide to give the lignin-based carbon aerogel excellent light and heat conductivity, which can quickly heat up under sunlight, thereby reducing the viscosity of crude oil, promoting efficient adsorption of crude oil, and successfully achieving oil-water separation.
[0031] 5. The lignin-based carbon aerogel of the present invention has a simple preparation process, low production cost, good hydrophobic and oil-absorbing properties, and excellent light and heat conduction capabilities, and is suitable for treating crude oil problems in seawater pollution.
[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a photograph of the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel of Example 1 of the present invention.
[0034] Figure 2This is a picture of the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel of Example 1 of the present invention adsorbing crude oil under simulated sunlight. DETAILED DESCRIPTION
[0035] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a photosensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0036] The following materials or reagents, unless otherwise specified, were commercially available.
[0037] Some embodiments of the present invention provide a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which includes the following raw materials in parts by weight: 56-82 parts of lactic acid; 18-44 parts of choline chloride; 5-12.5 parts of alkali lignin; 5-12.5 parts of resorcinol; 30-40 parts of formaldehyde solution; 1-3 parts of pore-forming agent; 1-2 parts of photothermal sensor; and 5-10 parts of hydrophobic agent.
[0038] In the above technical scheme, lactic acid and choline chloride form a DES (a low eutectic solvent composed of lactic acid and choline chloride) solution of common soluble alkali lignin; alkali lignin and resorcinol act as carbon sources and react with formaldehyde after formaldehyde is added; formaldehyde solution acts as a cross-linking agent, i.e., it undergoes a cross-linking reaction with alkali lignin and resorcinol to form a cross-linked network of methylene bonds and methylene ether bonds, so that the sol-gel process is successful and the hydrogel is successfully prepared; the pore-forming agent is soluble in DES and does not participate in the previous reaction, and forms pores, expands, and foams the gel during the carbonization process; the photothermal sensor gives the carbon aerogel excellent absorption of sunlight and conversion of sunlight into thermal energy, thereby reducing the viscosity of crude oil and quickly adsorbing crude oil.
[0039] Lactic acid and choline chloride are the solvent system of DES (choline chloride / lactic acid deep eutectic solvent), wherein the addition amount of lactic acid is 56-82 parts, and the addition amount of chlorine is 18-44 parts. Among them, it is known through experiments that in the case of 75 parts of lactic acid and 25 parts of choline chloride, that is, when the amount ratio of substance is 7:1, the amount of dissolved alkali lignin is more, and the formed hydrogel is fuller and moisturized, and will not shrink and wrinkle. Therefore, the most preferred is 75 parts of lactic acid and 25 parts of choline chloride.
[0040] Alkali lignin and resorcinol are carbon sources. The total amount of carbon source can be successfully cross-linked at 10-25 parts. If it is greater than 25 parts, it cannot be completely dissolved when the amount added is too much; if it is less than 10 parts, the amount added is too little, and the mechanical properties of the formed hydrogel are too poor and easy to break or the hydrogel cannot be formed at all. After various ratio experiments, it was found that the hydrogel formed by adding 20 parts of carbon source has the best mechanical properties, and the porosity after carbonization is also relatively higher. When alkali lignin accounts for up to 50% of the total mass of the carbon source, a gel can still be formed, and the mechanical properties are excellent. When the amount of alkali lignin added is more than 50%, a gel cannot be formed. For this reason, the preferred amount of alkali lignin added in the present invention is 10 parts, and the preferred amount of resorcinol added is 10 parts.
[0041] The concentration of the formaldehyde solution is 37wt%. As a crosslinking agent, the amount of formaldehyde solution added can affect the speed of gel formation and gel properties. If the amount added is greater than 40 parts, too much addition may lead to too many crosslinking points, forming a large number of crosslinked structures, affecting the uniformity and physical properties of the polymer. If the amount added is less than 30 parts, too little addition may lead to incomplete crosslinking reaction, resulting in poor performance of the polymer in various aspects, such as poor mechanical properties, poor mechanical properties, etc. Considering the performance of the polymer in various aspects, the present invention preferably adds 30-40 parts of formaldehyde solution.
[0042] The function of the pore former is to etch into pores. If the amount of the pore former added is greater than 3 parts, the excessive amount added will cause excessive expansion and deformation, reducing the mechanical properties of the carbon aerogel. If the amount of the pore former added is less than 1 part, the amount added is too little, the pore-forming effect is weak, and the specific surface area and porosity will not be too high. The pore former can be selected from one of zinc chloride, aluminum chloride and sodium chloride. Considering the pore-forming effect and the influence on the gel, the present invention preferably adds 3 parts of zinc chloride, which not only has an excellent pore-forming effect, but also does not cause excessive expansion and etching of the carbon aerogel.
[0043] The function of the photothermal sensor is to increase its photothermal sensing ability. If the amount of the photothermal sensor added is less than 1 part, the amount added is too little, the heat transfer capacity is reduced, and the photothermal sensing effect is not good. If the amount of the photothermal sensor added is more than 2 parts, the amount added is too much, the photothermal sensing effect is not significantly increased, but the cost will be increased. The photothermal sensor can be one of nano-iron tetroxide, graphene oxide and carbon nanotubes. Considering the photothermal conversion ability, the present invention preferably adds 2 parts of nano-iron tetroxide.
[0044] The effect of hydrophobic agent is hydrophobic modification, which increases roughness by attaching to the sample surface, reduces solid surface tension, thereby achieving a hydrophobic effect. If the addition of hydrophobic agent is less than 5 parts, the addition is too little, it is difficult to cover the entire sample surface and the inner side, and the hydrophobic effect will greatly decrease. If the addition of hydrophobic agent is greater than 10 parts, the addition is too much, and the cost will be increased. The hydrophobic agent can select one of methyltrichlorosilane, trimethylchlorosilane and triisopropylchlorosilane. Considering saving time and saving cost, the present invention preferably adds 5 parts of methyltrichlorosilane for the best.
[0045] Some embodiments of the present invention also provide a method for preparing the above-mentioned light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0046] (1) stirring the formulated amount of choline chloride and lactic acid with a magnetic stirrer to form a uniform transparent solution;
[0047] (2) Add the formulated amount of alkali lignin and resorcinol to the solution, and continue stirring with a magnetic stirrer until dissolved;
[0048] (3) Continue to add the formulated amount of pore-forming agent to the solution and continue to stir with a magnetic stirrer until dissolved;
[0049] (4) adding a formulated amount of photothermal sensor agent to the solution, and performing ultrasonic treatment with an ultrasonic cleaner until the photothermal sensor agent is evenly dispersed;
[0050] (5) adding formaldehyde solution dropwise into the solution and stirring evenly with a magnetic stirrer; considering cost, efficiency and safety, the concentration of the formaldehyde solution is set to 37 wt %.
[0051] (6) The solution is introduced into a mold, placed in an oven for heating and reaction until gelation occurs, and then dried; the mold is a cylindrical mold made of silica gel with a depth of 1 cm and a diameter of 2 cm.
[0052] (7) taking out the dried gel and placing it in a tubular furnace to carbonize it into carbon aerogel;
[0053] (8) The carbon aerogel is placed in a dryer and chemical vapor deposition is performed using a methyltrichlorosilane hydrophobic agent to obtain the target lignin-based carbon aerogel.
[0054] In some optional embodiments, in step (1), the magnetic stirrer stirs at a speed of 100-200 r / min for 20-40 min. If the speed is lower than 100 r / min, the DES will be mixed too slowly; if the speed is higher than 200 r / min, bubbles will be generated during the stirring process, and a vacuum drying oven will be required for degassing, resulting in a waste of time. If the speed is lower than 20 min, the stirring is likely to be uneven; if the speed is higher than 40 min, the stirring is ineffective and time is wasted.
[0055] In some optional embodiments, the magnetic stirrer in step (2) stirs at a speed of 300-500 r / min for 2 hours; if it is less than 300 r / min, the contact area between the alkali lignin and the solvent is small, the lower layer dissolves, and the upper layer is not easy to contact with the solvent; if it is greater than 500 r / min, the stirring is too fast, which easily produces the illusion that it seems to be dissolved, but in fact it is just the solution covering the alkali lignin. The alkali lignin dissolves slowly and needs to be added in small amounts and multiple times, otherwise it cannot be completely dissolved, and a total of 2 hours is required.
[0056] In some optional embodiments, in step (3), the magnetic stirrer stirs at a speed of 500-600 r / min for 20-40 min; low speed makes it difficult to drive the zinc chloride that has sunk to the bottom to dissolve, so a high speed is required to drive the zinc chloride. A speed greater than 600 r / min will cause bubbles to form in the solution, and a vacuum drying oven is required for degassing; a speed less than 500 r / min will make it difficult to effectively drive the zinc chloride to dissolve. When zinc chloride is added, the zinc chloride has a large density and will sink to the bottom, requiring a higher speed to drive and promote its dissolution. It can be completely dissolved in 20-40 min, and its dissolution can also be observed with the naked eye. If there are no zinc chloride particles, it is completely dissolved. In step (4), the ultrasonic cleaner is set at 20-30°C for ultrasonic treatment for 10-20 min; the ultrasonic cleaner generally does not work below 20°C, and the water temperature can only be manually increased, and the water temperature cannot be lowered; when it is higher than 30°C, it leads to a waste of preheating time and energy consumption. Less than 10 min can easily lead to uneven dispersion visible to the naked eye; more than 20 min wastes time and energy consumption. In step (5), the magnetic stirrer stirs at a speed of 100-200 r / min for 10-20 min. Adding the formaldehyde solution is liquid into liquid, which is easier to mix evenly than the previous solid into liquid. And no high speed is required to promote its mixing. If it is less than 100 r / min, the mixing speed will slow down; if it is greater than 200 r / min, the solution will easily foam and must be degassed in a vacuum drying oven, which wastes time and increases energy consumption. If it is less than 10 min, the mixing time is too short and may not be mixed evenly; if it is greater than 20 min, it wastes time and increases energy consumption.
[0057] In some optional embodiments, in step (6), the mold is sealed in an oven and the gelation reaction is carried out at 85-105°C for 40-60 minutes; after gelation, the mold is no longer sealed, and it is continued to be dried and aged at 90°C for 2h-3h. The phenolic cross-linking gel reaction is carried out at a high temperature above 85°C. Through a large number of experiments, it is found that the time required for gelation at 90°C is less than 85°C; and there is no significant difference between the gelation time at 90°C and 95°C, 100°C, and 105°C. Considering energy saving and reaction time, the present invention selects 85-105°C for gelation reaction. In general, gelation can be successful within 40-60 minutes. After a large number of tests, it is found that the morphological characteristics and mechanical properties of the sample aged at room temperature for 72h are far inferior to those of the sample aged at high temperature of 90°C for 3h. And continuing to dry and age at 85-105°C is also more convenient to operate the experimental instrument, without the need for adjustment and preheating and cooling. After a large number of tests, it was found that if the aging time is less than 2 hours, the mechanical properties of the gel with a short aging time are very different from those of the gel aged for 3 hours; however, the mechanical properties of the gel after aging for 3 hours are not significantly different from those of the gel aged for a longer time. Therefore, the present invention selects aging for 2h-3h, and aging at 90°C for 3h is optimal.
[0058] In some optional embodiments, in step (7), high-temperature carbonization is carried out in a tubular furnace under the protection of an inert gas; the material is heated to 950-1000°C at a heating rate of 4-6°C / min, kept warm for 1.5-3 hours, and then cooled to room temperature at a cooling rate of 1-2°C / min. The inert gas can be selected from nitrogen, hydrogen, nitrogen, argon or helium with a purity of 99%, preferably nitrogen, to promote the hardening of the material. If it is greater than 6°C / min, the tubular furnace heats up too quickly, which may cause the material in the furnace to be subjected to an excessively high temperature gradient in a short period of time, thereby destroying its structure, and also damage the structure of the tubular furnace body, affecting its service life; if it is less than 4°C / min, the tubular furnace heats up too slowly, affecting the experimental process. If zinc chloride is selected as a pore-forming agent, because the boiling point of zinc is 907°C, zinc needs to leave the tubular furnace under the drive of the protective gas after pore formation, so it needs to be heated to above 900°C. The insulation process is to increase the degree of carbonization, fully react, and fully separate zinc. If the insulation time is less than 1.5h, the time is too short to ensure complete reaction; if the insulation time is more than 3h, the time is too long, which will affect the service life of the tube furnace, delay the experimental process, and waste time. Generally, there are requirements for the maximum cooling speed of the tube furnace. The fastest cooling speed of most existing tube furnaces is 2℃ / min or natural speed cooling. The reason is that sudden changes in temperature can easily cause cracks in the furnace and cause certain impacts on the heating elements. Slow cooling can protect the tube furnace while reducing energy consumption.
[0059] In some optional embodiments, in step (8), methyltrichlorosilane is added 1-2 times every 1 hour in a small amount and multiple times, for a total of 4-6 times. Considering the attachment of methyltrichlorosilane to the surface of the carbon aerogel and the modification cost, adding once per hour is optimal. After a large number of experiments, it was found that the effect after 5 consecutive modifications was the best. The water contact angle of less than 4 times increases with the number of modifications, but after more than 6 times, there is no obvious change. Therefore, 5 times is optimal.
[0060] In some optional embodiments, the preparation method comprises the following steps:
[0061] (1) Stir the above-mentioned choline chloride and lactic acid in the above-mentioned amounts by weight at a speed of 10-200 r / min for 20-40 min using a magnetic stirrer to form a transparent uniform solution.
[0062] (2) In the solution, use the method of adding small amounts and multiple times, divide it into 10 parts, add the above-mentioned mass parts of alkali lignin and resorcinol in turn, and continue to stir with a magnetic stirrer at a speed of 300-500r / min for 2h until it is completely dissolved. The addition of alkali lignin and resorcinol needs to be done in small amounts and multiple times. After a large number of experiments, alkali lignin and resorcinol are used as carbon sources and added every 10-15min. This can dissolve alkali lignin more quickly, greatly improving the success rate. For example, divide alkali lignin into 10 parts and resorcinol into 10 parts, then the first time, alkali lignin and resorcinol are 1 part each; then the second time, alkali lignin and resorcinol are 1 part each; then the third time, alkali lignin and resorcinol are 1 part each; continue 10 times.
[0063] (3) Continue to add the above-mentioned pore-forming agent in parts by weight to the solution, and continue to stir with a magnetic stirrer at a speed of 500-600 r / min for 20-40 min until it is completely dissolved.
[0064] (4) Add the above-mentioned amount of nano-iron tetroxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 20-30° C. for 10-20 minutes until the nano-iron tetroxide is evenly dispersed.
[0065] (5) Add the above-mentioned formaldehyde solution by weight dropwise into the solution, and stir with a magnetic stirrer at a speed of 100-200 r / min for 10-20 min until the mixture is uniformly mixed.
[0066] (6) The solution is introduced into the mold, and the mold is sealed and placed in an oven for gelation reaction at 85-105°C for 40-60 minutes; after gelation, the mold is no longer sealed, and it is dried and aged at 90°C for 3 hours. The mold is sealed and then placed in an oven to prevent evaporation and wrinkles during gelation. After the previous sealed gelation, the sample has been fixed. The mold is no longer sealed and is placed in an oven at 90°C, which is equivalent to not only aging and curing the gel, but also drying out the liquid moisture in the body.
[0067] (7) Take out the dried gel and carbonize it at high temperature in a tube furnace under the protection of inert gas N2 (purity is greater than or equal to 99.99%); heat it to 950-1000°C at a heating rate of 4-6°C / min, and keep it at this temperature for 1.5-3 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0068] (8) The carbon aerogel is placed in a dryer, and 5-10 parts of a hydrophobic agent are added once every 1 hour for a total of 5 times in a small amount and multiple times, and chemical vapor deposition (CVD) is performed to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0069] Some embodiments of the present invention also provide a use of a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel in oil-water separation.
[0070] In some optional embodiments, the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel has an adsorption rate of 8.21 g / g-10.1 g / g for various oils and organic matter, so that the recycling rate of the lignin-based carbon aerogel after 10 uses is 94-95%.
[0071] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0072] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0073] Example 1
[0074] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0075] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0076] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0077] (3) Add 0.3 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0078] (4) Add 0.2 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0079] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0080] (6) The solution was introduced into a mold, and the mold was sealed and placed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0081] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0082] (8) The carbon aerogel is placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) is added once every 1 hour for a total of 5 times by chemical vapor deposition (CVD) to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0083] Figure 1 This is a photo of the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel of Example 1. Figure 1 It can be seen that the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel obtained in this embodiment is a carbon aerogel with a hard texture, a silver-black color, a metallic luster, and pores visible to the naked eye. Figure 1 From the cross-sectional view, we can see that there are a large number of pores inside, which provide a lot of storage space for oil absorption.
[0084] Figure 2This is a diagram showing the photosensitive and hydrophobic oil-absorbing lignin-based carbon aerogel of Example 1 of the present invention adsorbing crude oil under simulated sunlight. Figure 2 As shown in the figure, when the carbon aerogel comes into contact with crude oil with high viscosity, under the irradiation of a xenon lamp simulating the intensity of one sun, the lignin-based carbon aerogel of the present invention is sensitive to light and heats up rapidly, causing the crude oil in contact with it to heat up rapidly as well. This reduces the viscosity of the crude oil and completes the adsorption of the crude oil in less than 2 seconds, taking only 1.8 seconds. Figure 2 The excellent adsorption effect of the present invention on grease substances is significantly demonstrated.
[0085] Example 2
[0086] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0087] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0088] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0089] (3) Add 0.3 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0090] (4) Add 0.1 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0091] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0092] (6) The solution was introduced into a mold, and the mold was sealed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0093] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0094] (8) The carbon aerogel was placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) was added once every 1 h for a total of 5 times by chemical vapor deposition (CVD) to obtain the target lignin-based carbon aerogel.
[0095] Example 3
[0096] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0097] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0098] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0099] (3) Add 0.2 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0100] (4) Add 0.2 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0101] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0102] (6) The solution was introduced into a mold, and the mold was sealed and placed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0103] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0104] (8) The carbon aerogel is placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) is added once every 1 hour for a total of 5 times by chemical vapor deposition (CVD) to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0105] Example 4
[0106] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0107] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0108] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0109] (3) Add 0.2 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0110] (4) Add 0.1 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0111] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0112] (6) The solution was introduced into a mold, and the mold was sealed and placed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0113] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0114] (8) The carbon aerogel is placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) is added once every 1 hour for a total of 5 times by chemical vapor deposition (CVD) to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0115] Example 5
[0116] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0117] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0118] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0119] (3) Add 0.1 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0120] (4) Add 0.2 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0121] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0122] (6) The solution was introduced into a mold, and the mold was sealed and placed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0123] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0124] (8) The carbon aerogel is placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) is added once every 1 hour for a total of 5 times by chemical vapor deposition (CVD) to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0125] Example 6
[0126] This embodiment provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0127] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0128] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0129] (3) Add 0.1 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0130] (4) Add 0.1 g of nano-ferroferric oxide to the solution, and use an ultrasonic cleaner to perform ultrasonic treatment at 25° C. for 15 min until the nano-ferroferric oxide is evenly dispersed.
[0131] (5) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0132] (6) The solution was introduced into a mold, and the mold was sealed and placed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 hours.
[0133] (7) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0134] (8) The carbon aerogel is placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) is added once every 1 hour for a total of 5 times by chemical vapor deposition (CVD) to obtain the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel.
[0135] Comparative Example 1
[0136] This comparative example provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0137] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0138] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0139] (3) Add 0.3 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0140] (4) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0141] (5) The solution was introduced into a mold, and the mold was sealed in an oven and subjected to gelation reaction at 90° C. for 1 h. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 h.
[0142] (6) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0143] (7) The carbon aerogel was placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) was added once every 1 h for a total of 5 times by chemical vapor deposition (CVD) to obtain the target lignin-based carbon aerogel.
[0144] Comparative Example 2
[0145] This comparative example provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0146] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0147] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0148] (3) Add 0.2 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0149] (4) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0150] (5) The solution was introduced into a mold, and the mold was sealed in an oven and subjected to gelation reaction at 90° C. for 1 h. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 h.
[0151] (6) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0152] (7) The carbon aerogel was placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) was added once every 1 h for a total of 5 times by chemical vapor deposition (CVD) to obtain the target lignin-based carbon aerogel.
[0153] Comparative Example 3
[0154] This comparative example provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0155] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0156] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0157] (3) Add 0.1 g of zinc chloride to the solution and continue stirring with a magnetic stirrer at 600 r / min for 30 min until it is completely dissolved.
[0158] (4) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0159] (5) The solution was introduced into a mold, and the mold was sealed in an oven and subjected to gelation reaction at 90° C. for 1 h. After gelation, the mold was no longer sealed and continued to be dried and aged at 90° C. for 3 h.
[0160] (6) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0161] (7) The carbon aerogel was placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) was added once every 1 h for a total of 5 times by chemical vapor deposition (CVD) to obtain the target lignin-based carbon aerogel.
[0162] Comparative Example 4
[0163] This comparative example provides a method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, which comprises the following steps:
[0164] (1) 2.5 g of choline chloride and 7.5 g of lactic acid were stirred at 150 r / min using a magnetic stirrer for 30 min until a transparent uniform solution was formed.
[0165] (2) Add 1 g of alkali lignin and 1 g of resorcinol in 10 portions to the solution in small amounts and multiple times, and continue stirring at 400 r / min with a magnetic stirrer for 2 h until they are completely dissolved.
[0166] (3) 3 g of formaldehyde solution (concentration of 37 wt%) was added dropwise into the solution using a pipette, and the mixture was stirred at a speed of 150 r / min for 15 min using a magnetic stirrer until the mixture was uniformly mixed.
[0167] (4) The solution was introduced into a mold, and the mold was sealed in an oven for gelation reaction at 90° C. for 1 hour. After gelation, the mold was no longer sealed, and drying and aging were continued at 90° C. for 3 hours.
[0168] (5) Take out the dried gel and carbonize it at high temperature in a tubular furnace under the protection of inert gas N2 (purity is 99.99%); heat it to 950°C at a heating rate of 5°C / min and keep it at that temperature for 2 hours; then cool it to room temperature at a cooling rate of 2°C / min and take it out.
[0169] (6) The carbon aerogel was placed in a dryer, and 0.5 g of methyltrichlorosilane (0.1 g) was added once every 1 h for a total of 5 times by chemical vapor deposition (CVD) to obtain the target lignin-based carbon aerogel.
[0170] The photosensitive and hydrophobic and oil-absorbing lignin-based carbon aerogels prepared in Examples 1-6 and the lignin-based carbon aerogels prepared in Comparative Examples 1-4 were subjected to performance tests. The test results are shown in Table 1.
[0171] Table 1 Performance data of Examples 1-6 and Comparative Examples 1-4
[0172]
[0173]
[0174] From the data in Table 1, it can be seen that 2 parts (0.2 g) of nano-iron tetroxide are added to each of Example 1, Example 3 and Example 5, and only the amount of zinc chloride added is different in the preparation (0.3 g for Example 1, 0.2 g for Example 3 and 0.1 g for Example 5). The specific surface areas of Example 1, Example 3 and Example 5 are 729.18 m 2 / g, 521.34m 2 / g and 172.18m 2 / g. In Example 2, Example 4 and Example 6, 1 part (0.1 g) of nano-iron tetroxide is added. Only the amount of zinc chloride added is different in the preparation (0.3 g in Example 2, 0.2 g in Example 4 and 0.1 g in Example 6). The specific surface areas of Example 2, Example 4 and Example 5 are 716.94 m 2 / g, 510.06m 2 / g and 164.29m 2 / g. Comparative Examples 1, 2, 3 and 4 did not add nano-iron tetroxide, and only the amount of zinc chloride added was different in the preparation (0.3g for Comparative Example 1, 0.2g for Comparative Example 2, 0.1g for Comparative Example 3, and no zinc chloride was added for Comparative Example 4). The specific surface areas of Comparative Examples 1, 2, 3 and 4 were 667.73 m 2 / g, 491.03m 2 / g, 151.99m 2 / g and 18.98m 2 / g. From the comparison of the above three groups of data, it can be seen that the specific surface area of lignin carbon aerogel increases significantly with the increase of zinc chloride addition, indicating that the addition of zinc chloride can significantly improve the pore-forming effect of the lignin-based carbon aerogel of the present invention, thereby facilitating better adsorption of oil.
[0175] As can be seen from the data in Table 1, Example 1, Example 3 and Example 5 all add 2 parts (0.2g) of nano-iron tetroxide, and only the addition amount of zinc chloride is different in the preparation (Example 1 is 0.3g, Example 3 is 0.2g, and Example 5 is 0.1g), and the pore volumes of Example 1, Example 3 and Example 5 are 0.2640ml / g, 0.1906ml / g, and 0.0685ml / g, respectively. Example 2, Example 4 and Example 6 all add 1 part (0.1g) of nano-iron tetroxide, and only the addition amount of zinc chloride is different in the preparation (Example 2 is 0.3g, Example 4 is 0.2g, and Example 6 is 0.1g), and the pore volumes of Example 2, Example 4 and Example 6 are 0.2371ml / g, 0.1844ml / g and 0.0502ml / g, respectively. Comparative Examples 1, 2, 3 and 4 were all free of nano-iron tetroxide. Only the amount of zinc chloride added was different in the preparation (0.3 g for Comparative Example 1, 0.2 g for Comparative Example 2, 0.1 g for Comparative Example 3, and no zinc chloride was added for Comparative Example 4). The pore volumes of Comparative Examples 1, 2, 3 and 4 were 0.2279 ml / g, 0.1805 ml / g, 0.0421 ml / g and 0.0040 ml / g, respectively. From the comparison of the above three groups of data, it can be seen that the total pore volume of the lignin carbon aerogel increases significantly with the increase of the amount of zinc chloride added, which again shows that the addition of zinc chloride significantly improves the pore-forming effect of the lignin-based carbon aerogel of the present invention, thereby facilitating better adsorption of grease.
[0176] As can be seen from the data in Table 1, Example 1, Example 3 and Example 5 all add 2 parts (0.2g) of nano-ferrosoferric oxide, and only the addition amount of zinc chloride is different in the preparation (0.3g for Example 1, 0.2g for Example 3, and 0.1g for Example 5), and the water contact angles of Example 1, Example 3 and Example 5 are 152°, 126° and 118°, respectively. Example 2, Example 4 and Example 6 all add 1 part (0.1g) of nano-ferrosoferric oxide, and only the addition amount of zinc chloride is different in the preparation (0.3g for Example 2, 0.2g for Example 4, and 0.1g for Example 6), and the water contact angles of Example 2, Example 4 and Example 5 are 139°, 130° and 114°, respectively. Comparative Examples 1, 2, 3 and 4 did not add nano-ferroferric oxide, and only the amount of zinc chloride added was different in the preparation (0.3 g for Comparative Example 1, 0.2 g for Comparative Example 2, 0.1 g for Comparative Example 3, and no zinc chloride was added for Comparative Example 4). The water contact angles of Comparative Examples 1, 2, 3 and 4 were 127°, 124°, 117° and 109°, respectively. From the comparison of the above three groups of data, it can be seen that the water contact angle of the lignin carbon aerogel increases significantly with the increase of the amount of zinc chloride added, indicating that the addition of zinc chloride improves the non-polarity or low polarity of the lignin-based carbon aerogel of the present invention, making the lignin-based carbon aerogel product and water molecules less attractive to each other, thereby significantly improving the hydrophobic effect of the lignin-based carbon aerogel of the present invention, so as to facilitate better adsorption of grease.
[0177] From the data in Table 1, it can be seen that 3 parts (0.3 g) of zinc chloride are added to Example 1, Example 2 and Comparative Example 1, and only the amount of nano-iron tetroxide added is different in the preparation (0.2 g for Example 1, 0.1 g for Example 2, and no nano-iron tetroxide is added to Comparative Example 1). The specific surface areas of Example 1, Example 2 and Comparative Example 1 are 729.18 m 2 / g, 716.94m 2 / g and 667.73m 2 / g. In Example 3, Example 4 and Comparative Example 2, 2 parts (0.2g) of zinc chloride are added. Only the amount of nano-ferroferric oxide added is different in the preparation (0.2g in Example 3, 0.1g in Example 4, and no nano-ferroferric oxide is added in Comparative Example 2). The specific surface areas of Example 3, Example 4 and Comparative Example 2 are 521.34m 2 / g, 510.06m 2 / g and 491.03m 2 / g. In Example 5, Example 6 and Comparative Example 3, 1 part (0.1 g) of zinc chloride is added. Only the amount of nano-ferroferric oxide added is different in the preparation (0.2 g in Example 5, 0.1 g in Example 6, and no nano-ferroferric oxide is added in Comparative Example 3). The specific surface areas of Example 5, Example 6 and Comparative Example 3 are 172.18 m 2 / g, 164.29m 2 / g and 151.99m 2 / g. From the comparison of the above three groups of data, it can be seen that the addition of nano-ferroferric oxide can slightly increase the specific surface area of lignin-based carbon aerogel, forming more pores, thereby adsorbing more oil.
[0178] As can be seen from the data in Table 1, Example 1, Example 2 and Comparative Example 1 all add 3 parts (0.3g) of zinc chloride, and only the addition amount of nano ferroferric oxide is different in the preparation (Example 1 is 0.2g, Example 2 is 0.1g, and Comparative Example 1 does not add nano ferroferric oxide), and the pore volumes of Example 1, Example 2 and Comparative Example 1 are 0.2640ml / g, 0.2371ml / g and 0.2279ml / g respectively. Example 3, Example 4 and Comparative Example 2 all add 2 parts (0.2g) of zinc chloride, and only the addition amount of nano ferroferric oxide is different in the preparation (Example 3 is 0.2g, Example 4 is 0.1g, and Comparative Example 2 does not add nano ferroferric oxide), and the pore volumes of Example 3, Example 4 and Comparative Example 2 are 0.1904ml / g, 0.1844ml / g and 0.1805ml / g respectively. In Example 5, Example 6 and Comparative Example 3, 1 part (0.1 g) of zinc chloride is added. Only the amount of nano-ferroferric oxide added is different in the preparation (0.2 g in Example 5, 0.1 g in Example 6, and no nano-ferroferric oxide is added in Comparative Example 3). The pore volumes of Example 5, Example 6 and Comparative Example 3 are 0.0685 ml / g, 0.0502 ml / g and 0.0421 ml / g, respectively. From the comparison of the above three groups of data, it can be seen that the addition of nano-ferroferric oxide can slightly increase the total pore volume of lignin-based carbon aerogel, form more pores, and thus adsorb more grease.
[0179] It can be seen from the data in Table 1 that Example 1, Example 3, and Example 5 all add 2 parts (0.2g) of nano-iron tetroxide, and the fastest heating rates under a standard sunlight simulation are 161°C / s, 157°C / s, and 152°C / s, respectively; Example 2, Example 4, and Example 6 all add 2 parts (0.1g) of nano-iron tetroxide, and the fastest heating rates under a standard sunlight simulation are 67°C / s, 71°C / s, and 65°C / s, respectively; Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 all do not add nano-iron tetroxide, and the fastest heating rates under a standard sunlight simulation are 12°C / s, 11°C / s, 12°C / s, and 10°C / s, respectively. The above results show that lignin-based carbon aerogels without the addition of nano-iron tetroxide do not have a good ability to convert light energy into heat energy. However, with the increase in the amount of nano-iron tetroxide added, the speed and peak value of the light energy conversion of lignin-based carbon aerogels also increase significantly.
[0180] Application Examples
[0181] The lignin-based carbon aerogel prepared in Example 1 was used to adsorb crude oil under simulated sunlight. Figure 2 .
[0182] Table 2 Adsorption performance of various substances in Examples 1-6 and Comparative Examples 1-4 under simulated sunlight
[0183]
[0184] Depend on Figure 2 It can be seen intuitively that under sunlight, the present invention can quickly adsorb crude oil in only 1.8 seconds. This is due to its excellent photothermal sensing ability. From the data in Table 2, it can be seen that Example 1 is the optimal embodiment. The maximum adsorption rates of corn oil, soybean oil, rapeseed oil, peanut oil, pump oil and silicone oil in Example 1 are 8.71g / g, 10.1g / g, 9.33g / g, 8.21g / g, 8.67g / g and 8.40g / g, respectively, showing the good adsorption effect of the present invention on common oils and fats. The maximum adsorption rates of Example 1 for ethanol, isopropanol, cyclohexane and ethyl acetate are 9.66g / g, 8.57g / g, 8.28g / g and 8.61g / g, respectively, showing the good adsorption effect of the lignin-based carbon aerogel of the present invention on common organic solvents. Since the viscosity of crude oil itself is much higher than that of other oils, the adsorption performance of the lignin-based carbon aerogel of the present invention is lower than that of other oils and organic solvents. The maximum adsorption capacity of crude oil per 1g of Example 1 is 5.29g.
[0185] The only difference between Example 1, Example 2 and Comparative Example 1 is the amount of nano-iron tetroxide added, and the rest, such as the amount of zinc chloride added and the preparation process, are the same. As can be seen from the data in Table 2, when adsorbing common oils such as corn oil and soybean oil and common organic solvents such as ethanol and cyclohexane, the adsorption capacity of Example 1, Example 2 and Example 3 does not show a large difference in data (such as the maximum adsorption rates of corn oil in Example 1, Example 2 and Example 3 are 8.71g / g, 8.52g / g, and 8.61g / g, respectively). This shows that the addition of nano-iron tetroxide has no negative impact on the adsorption of common oils and common organic solvents by the lignin-based carbon aerogel of the present invention.
[0186] As can be seen from the data in Table 2, Example 1, Example 3 and Example 5 all add 2 parts (0.2g) of nano ferrosoferric oxide, and only the addition amount of zinc chloride is different in the preparation (0.3g for Example 1, 0.2g for Example 3, and 0.1g for Example 5). The maximum adsorption rates of soybean oil in Example 1, Example 3 and Example 5 are 10.1g / g, 4.99g / g and 1.02g / g, respectively. Example 2, Example 4 and Example 6 all add 1 part (0.1g) of nano ferrosoferric oxide, and only the addition amount of zinc chloride is different in the preparation (0.3g for Example 2, 0.2g for Example 4, and 0.1g for Example 6). The maximum adsorption rates of soybean oil in Example 2, Example 4 and Example 6 are 9.83g / g, 4.56g / g and 0.99g / g, respectively. Comparative Examples 1, 2, 3 and 4 were not added with nano-iron tetroxide. Only the amount of zinc chloride added was different in the preparation (0.3g for Comparative Example 1, 0.2g for Comparative Example 2, 0.1g for Comparative Example 3, and no zinc chloride was added for Comparative Example 4). The maximum adsorption rates of soybean oil in Comparative Examples 1, 2, 3 and 4 were 9.90g / g, 4.43g / g, 0.83g / g and 0.12g / g, respectively. From the above three groups of comparisons, it can be seen that the maximum adsorption rate of lignin carbon aerogel to soybean oil increases significantly with the increase of the amount of zinc chloride added, which intuitively shows that the addition of zinc chloride significantly improves the ability of the lignin-based carbon aerogel of the present invention to adsorb grease. In addition to soybean oil, other oils and organic solvents (such as corn oil, rapeseed oil, peanut oil, ethanol, cyclohexane, ethyl acetate, etc.) can equally prove that the addition of zinc chloride significantly improves the ability of the lignin-based carbon aerogel of the present invention to adsorb grease and organic solvents.
[0187] In terms of adsorption of crude oil, Example 1, Example 2 and Comparative Example 1 all added 3 parts (0.3g) of zinc chloride, and only the amount of nano ferroferric oxide added was different in the preparation (Example 1 was 0.2g, Example 2 was 0.1g, and Comparative Example 1 did not add nano ferroferric oxide), and the adsorption rates of crude oil in Example 1, Example 2 and Comparative Example 1 were 5.29g / g, 2.65g / g, and 0g / g, respectively. Example 3, Example 4 and Comparative Example 2 all added 2 parts (0.2g) of zinc chloride, and only the amount of nano ferroferric oxide added was different in the preparation (Example 3 was 0.2g, Example 4 was 0.1g, and Comparative Example 2 did not add nano ferroferric oxide), and the adsorption rates of crude oil in Example 3, Example 4 and Comparative Example 2 were 4.06g / g, 1.91g / g, and 0g / g, respectively. Example 5, Example 6 and Comparative Example 3 all add 1 part (0.1g) of zinc chloride, and only the amount of nano-iron tetroxide added is different in the preparation (Example 5 is 0.2g, Example 6 is 0.1g, and Comparative Example 3 does not add nano-iron tetroxide). The adsorption rates of crude oil in Example 5, Example 6 and Comparative Example 3 are 3.42g / g, 1.23g / g, and 0g / g, respectively. The reason is that the different amounts of nano-iron tetroxide added lead to different degrees of sunlight absorption and sensing capabilities. The addition of nano-iron tetroxide can greatly improve its photothermal sensing ability, and can greatly increase the surface temperature of the gel under the irradiation of 1 sunlight, and quickly heat up the crude oil by contacting the crude oil, reduce the viscosity of the crude oil, and achieve the effect of adsorbing the crude oil.
[0188] From the data in Table 2, it can be seen that the maximum adsorption rates of crude oil in Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 are 5.29g / g, 2.65g / g, 4.06g / g, 1.91g / g, 3.42g / g and 1.23g / g respectively. Among the 6 embodiments, the maximum adsorption rate of crude oil in the present invention is ranked as follows: Example 1> Example 3> Example 5> Example 2> Example 4> Example 6. Among them, Example 1, Example 3 and Example 5 all add 2 parts (0.2g) of nano-ferroferric tetroxide; Example 2, Example 4 and Example 6 all add 1 part (0.1g) of nano-ferroferric tetroxide; Example 1 and Example 2 all add 3 parts (0.3g) of zinc chloride; Example 3 and Example 4 all add 2 parts (0.2g) of zinc chloride; Example 5 and Example 6 all add 1 part (0.1g) of zinc chloride. In summary, it can be proved that the adsorption of crude oil by the present invention is jointly affected by zinc chloride and nano-ferroferric oxide. Among them, nano-ferroferric oxide gives the present invention excellent photothermal sensing ability, which reduces the viscosity of crude oil and is conducive to the rapid adsorption of the present invention; zinc chloride gives the present invention a large amount of pore volume and ultra-high specific surface area, greatly increasing the storage space for adsorption. The two work together to make the present invention excellent in the adsorption of grease, organic solvents, heavy oil and other aspects.
[0189] Combined with Table 1 and Table 2, from the mechanism analysis: after adding zinc chloride, zinc chloride is converted into zinc oxide at a temperature below 500 ° C. As the temperature rises, zinc oxide continues to react with the carbonized aerogel to form elemental zinc, carbon monoxide and carbon dioxide. As the reaction proceeds, a large amount of carbon is etched by zinc oxide, resulting in a large number of pores in the carbon aerogel. When the temperature rises to 950 ° C, the metallic zinc reaches the boiling point and evaporates, and is sent out with the protective gas nitrogen in the tubular furnace, and a large number of pores are left after etching. This phenomenon also shows that zinc chloride successfully manufactures pores. Therefore, as shown in the data of Example 3, Example 4, Example 5 and Example 6 in Table 1, the pore volume, average pore size and specific surface area of the product increase with the increase of the amount of zinc chloride added. Higher porosity, average pore size and specific surface area can provide the product with more space to absorb and store oils, and coupled with hydrophobic modification, its adsorption capacity is greatly improved. In summary, more zinc chloride addition can greatly improve the adsorption performance of this product.
[0190] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0191] The numerical range described in the present invention includes all the numerical values within the range, and includes the range value formed by any two numerical values within the range. Different numerical values of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.
[0192] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0193] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, characterized in that: The invention comprises the following raw materials in parts by weight: 56-82 parts of lactic acid; 18-44 parts of choline chloride; 5-12.5 parts of alkali lignin; 5-12.5 parts of resorcinol; 30-40 parts of formaldehyde solution; 1-3 parts of pore-forming agent; 1-2 parts of photothermal sensor; and 5-10 parts of hydrophobic agent.
2. The light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 1, characterized in that: The concentration of the formaldehyde solution is 37 wt %; the pore-forming agent is selected from one of zinc chloride, aluminum chloride and sodium chloride.
3. The light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 1, characterized in that: The photothermal sensing agent is selected from one of nano-ferroferric oxide, graphene oxide and carbon nanotubes; the hydrophobic agent can be selected from one of methyltrichlorosilane, trimethylchlorosilane and triisopropylchlorosilane.
4. A method for preparing a light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel, characterized in that: The steps include: S1. Stir choline chloride and lactic acid to form a transparent solution; then add alkali lignin and resorcinol to the transparent solution and continue to stir until dissolved; then continue to add a pore-forming agent and continue to stir until dissolved; then add a photothermal sensor and perform ultrasound until the photothermal sensor is evenly dispersed; then drop a formaldehyde solution and stir evenly; S2: heating the solution obtained in step S1 in a sealed environment until it is gelled, and then continuing to dry and age in an open environment; S3 taking out the gel dried in step S2 and carbonizing it in the presence of an inert gas to form a carbon aerogel; S4: subjecting the carbon aerogel obtained in step S3 to chemical vapor deposition in a dry environment using a hydrophobic agent to obtain the light-sensitive, hydrophobic, and oil-absorbing lignin-based carbon aerogel.
5. The method for preparing the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 4, characterized in that: In step S1, the stirring speed of the choline chloride and lactic acid is 100-200 r / min, and the stirring time is 20-40 min; the stirring speed after adding the alkali lignin and resorcinol is 300-500 r / min, and the time is 20-40 min; the stirring speed after adding the pore-forming agent is 500-600 r / min, and the time is 20-40 min; the temperature of the ultrasound is 20-30° C., and the time is 10-20 min; The stirring speed after adding the formaldehyde solution is 100-200 r / min, and the time is 10-20 min.
6. The method for preparing the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 4, characterized in that: In step S2, the temperature of the heating reaction is 85-105°C, and the time is 40-60 minutes; the temperature of the drying and aging is 85-105°C, and the time is 2-3 hours.
7. The method for preparing the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 4, characterized in that: In step S3, the inert gas is selected from nitrogen, hydrogen, nitrogen, argon or helium with a purity of 99%; the carbonization parameters are set as follows: heating to 950-1000°C at a heating rate of 4-6°C / min, keeping warm for 1.5-3 hours, and then cooling to room temperature at a cooling rate of 1-2°C / min.
8. The method for preparing the light-sensitive and hydrophobic and oil-absorbing lignin-based carbon aerogel according to claim 4, characterized in that: In step S4, the hydrophobic agent is added in the following manner: 1-2 times every 1 hour, for a total of 4-6 times.
9. Application of a light-sensitive and hydrophobic oil-absorbing lignin-based carbon aerogel in oil-water separation, characterized in that: The light-sensitive and hydrophobic oil-absorbing lignin-based carbon aerogel comprises the following raw materials in parts by weight: 56-82 parts of lactic acid; 18-44 parts of choline chloride; 5-12.5 parts of alkali lignin; 5-12.5 parts of resorcinol; 30-40 parts of formaldehyde solution; 1-3 parts of pore-forming agent; 1-2 parts of photothermal sensor; and 5-10 parts of hydrophobic agent.
10. Use of the light-sensitive and hydrophobic oil-absorbing lignin-based carbon aerogel in oil-water separation as claimed in claim 9, characterized in that: The adsorption rate of the lignin-based carbon aerogel to various oils and organic matter is 8.21 g / g-10.1 g / g, so that the recycling rate of the lignin-based carbon aerogel after being used 10 times is 94%-95%.